POST-COLONIAL PERSPECTIVES IN HISTORY EDUCATION: IMPLEMENTATION AT A CBSE-AFFILIATED HIGH SCHOOL IN INDIA - Maureen Joanna Finny (Satmata: Journal of Historical Education Studies, 2024)
This study explores the implementation of post-colonial perspectives in history education at a CBSE-affiliated senior secondary school in India, with a specific focus on Kendriya Vidyalaya No. 2, New Delhi. The research aims to examine how teachers interpret and apply decolonized historical narratives in classroom practices and how students engage with these narratives. Utilizing a qualitative case study approach, data were collected through classroom observations, semi-structured interviews with three history teachers, and focus group discussions involving twelve students. Thematic analysis revealed that while the CBSE curriculum includes post-colonial themes, their classroom realization is limited by exam-oriented pedagogy, insufficient teacher training, and systemic constraints. Most teachers rely heavily on lecture-based instruction and textbook summaries, with minimal integration of critical pedagogy or indigenous historiography. Students, although interested in local historical content, found lessons to be largely memorization-driven and lacking in interactive or analytical depth. The study’s novelty lies in its micro-level focus on the intersection between post-colonial theory and real classroom practice, offering empirical insights rarely explored in previous research. It also contributes a dual perspective—teacher and student—that enhances the understanding of practical challenges in educational reform. The findings suggest that meaningful integration of post-colonial perspectives requires systemic changes beyond curriculum revisions, including teacher professional development, alternative assessment models, and pedagogical innovation. This research provides valuable implications for post-colonial education globally, especially in nations seeking to reclaim historical narratives and promote critical, inclusive history education.